Improvement in Activities of Daily Living Among Danish Centenarians?—A Comparative Study of Two Centenarian Cohorts Born 20 Years Apart. (8th June 2017) - Rasmussen, Signe Høi; Thinggaard, Mikael; Højgaard, Majken Boris; Jeune, Bernard; Christensen, Kaare; Andersen-Ranberg, Karen
Abstract: Background: With the continued rise in the proportion of the oldest-old in high-income countries, it is of interest to know whether the functional health of today's oldest-olds is better or worse than in previous cohorts. Using two Danish centenarian birth cohorts born 20 years apart we aimed at investigating if the later born cohort had better functioning in terms of activities of daily living (ADL). Methods: Identification, methodology, and assessment instruments were identical in the 1895-West and 1915-West Birth Cohort Studies: All persons living in the western part of Denmark and turning 100 years old in 1995 and 2015, respectively. Data were collected through structured in-home interviews. Participation rates were 74% ( n = 106) and 79% ( n = 238), respectively. Results: The proportion of nondisabled women of the 1915-West cohort was more than twice as high compared to the 1895-West cohort and with corresponding lower proportions of moderately and severely disabled persons (17% vs 7%, 33% vs 40% and 50% vs 53% in the 1915-West and 1895-West cohorts, respectively, p = .047). Only nonsignificant improvements were seen among men in the 1915-West cohort. In both sexes, considerably higher proportions of the latest cohort used assistive devices than the former (statistically significant for the majority of assistive devices). Conclusion: This comparative study shows improvements in reported ADL in the later born cohort of centenarians, even though only significant among women. As women constitute the majority of the oldest-olds, our findings are encouraging from a public health care view.